Party politics: A contest perspective - Dominik Bruckner; Marco Sahm (Bamberg University, Bamberg Economic Research Group (BERG), 2024)
Intra-party contests, such as the US primaries, are often used to select a candidate for a subsequent cross-party election. A more accurate selection may improve the quality of the candidate but detract more resources from the subsequent campaign. We model this trade-off as a problem of contest design and show that extreme accuracy levels are optimal: maximum accuracy if the potential candidates are sufficiently heterogeneous, and a highly random selection otherwise. In an extension of our model, the heterogeneity between potential candidates reflects the degree of political polarization within a party. Our results explain varying primary designs within and between countries and shed light upon the paradox of limited competition within democratic parties.
Keywords: C72; D72; 330; Contest Design; Accuracy; Elections; Intra-Party Competition; Political Polarization